Maximum Power Point Tracking Approach Based on Temperature for PV Surface Using PSPICE Program - Hamed, Harith M Saeed; Kubba, Zainab M (Al-Nahrain Journal of Science, 2018)
This paper studies the effect of PV surface Temperature on PV panel output characteristics. Circuit simulator PSPICE is used to compose PV panel model at 75W, 4.8A and 21V. The behavior of PV model under varying conditions (solar insolation, temperature and PV panel surface temperature) is studied. The ABM feature of PSPICE is used to include the above parameters in PV PSPICE model and produced temperature dependent voltage. This voltage is converted to current with galvanic insulation by element Gploy with gain 0.8. This model defined as a hierarchal block in PSPICE library and could be called as individual source for any applications. The effect of PV surface temperature on its I-V curves specially the positions of the MPP,  is used to keep track of the MPP. Therefore, DC-DC boost converter was used to achieve this purpose. Boost converter was raised a PV panel voltage from 17V to 34V (for all variation of PV surface temperature 280K to 360K) also output current 4.4A for switching frequency 10kHz are selected.